Natural-Derived COX-2 Inhibitors as Anticancer Drugs: A Review of their Structural Diversity and Mechanism of Action - Mahboubi-Rabbani, Mohammad; Abbasi, Maryam; Zarghi, Afshin (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Cyclooxygenase-2 (COX-2) is a key-type enzyme playing a crucial role in cancer development, making it a target of high interest for drug designers. In the last two decades, numerous selective COX-2 inhibitors have been approved for various clinical conditions. However, data from clinical trials propose that the prolonged use of COX-2 inhibitors is associated with life-threatening cardiovascular side effects. The data indicate that a slight structural modification can help develop COX-2 selective inhibitors with comparative efficacy and limited side effects. In this regard, secondary metabolites from natural sources offer great hope for developing novel COX-2 inhibitors with potential anticancer activity. In recent years, various nature-derived organic scaffolds are being explored as leads for developing new COX-2 inhibitors. The current review attempts to highlight the COX-2 inhibition activity of some naturally occurring secondary metabolites, concerning their capacity to inhibit COX-1 and COX-2 enzymes and inhibit cancer development, aiming to establish a structure-activity relationship.
Keywords: COX-2 inhibitors